2020
DOI: 10.1038/s41598-020-75576-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diet and Apoe deficiency on retinal structure and function in mice

Abstract: To investigate the effects of a high-fat diet (HFD) and apolipoprotein E (Apoe) deficiency on retinal structure and function in mice. Apoe KO mice and wild-type C57BL/6J mice were given a low-fat diet (LFD) or a HFD for 32 weeks. Blood glucose, serum lipids, body weight and visceral fat weight were evaluated. Retinal sterol quantification was carried out by isotope dilution gas chromatography-mass spectrometry. The cholesterol metabolism related genes SCAP-SREBP expressions were detected by qRT-PCR. Retinal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“… 63 Several recent studies have shown that HFD significantly alters the rhythms of physiological function in the liver and brain. 20 , 44 , 46 , 69 , 82 Here, we show that HFD-induced metabolic stress also causes significant alterations in the immune-related transcriptome of lacrimal gland tissue. Moreover, an HFD changes the circadian phase and amplitude of trafficking of a variety of immune cells (mainly CD4 + and CD8 + T cells and neutrophils) to the lacrimal glands over a 24-hour cycle.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… 63 Several recent studies have shown that HFD significantly alters the rhythms of physiological function in the liver and brain. 20 , 44 , 46 , 69 , 82 Here, we show that HFD-induced metabolic stress also causes significant alterations in the immune-related transcriptome of lacrimal gland tissue. Moreover, an HFD changes the circadian phase and amplitude of trafficking of a variety of immune cells (mainly CD4 + and CD8 + T cells and neutrophils) to the lacrimal glands over a 24-hour cycle.…”
Section: Discussionmentioning
confidence: 58%
“… 15 18 Recent studies have demonstrated that HFD-fed mice showed various pathological alterations in retinal structure. 19 , 20 Mice fed an HFD for 10 days exhibited corneal dysfunction, including diminished corneal sensitivity and circadian activities (limbal neutrophil accumulation and epithelial cell division). 21 Following corneal abrasion, these mice showed delayed wound closure and nerve recovery and dysregulated leukocyte recruitment to the abraded cornea.…”
mentioning
confidence: 99%
“…To determine whether ischemia causes the severe inner retina degeneration in the ND group, we investigated flow in the inner retina blood vessels using fundus fluorescein angiography (FFA) 36 38 . We consistently found that blood flow was significantly delayed and decreased in ND retinas and to a lesser degree in LF retinas, whereas blood infiltration dynamics in HF retinas were similar to those in control retinas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, ocular ischemia with inner retina damage and outer retina sparing has been reported in rats with acute high IOP elevation 42 45 . FFA is a diagnostic method for vascular deformation, non-perfusion and leakage, which can be used to evaluate the retinal blood supply 36 38 . It revealed significantly decreased blood flow in the inner retina of the ND group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of the ApoE knockout combined with a HFD also results in lipidosis and inflammation in lung tissue through the toll-like receptor 4 (TLR4) pathway [ 23 ]. Furthermore, Cao et al also demonstrated an increase in ischemia susceptibility, inflammation, ganglion cell apoptosis, and retinal neovascularization in the ApoE knockout when combined with the administration of a HFD [ 24 ]. The accumulation of oxidized-LDL on tendons can decrease the functionality and induce a proliferative and matrix-degrading phenotype in tenocytes under ApoE knockout conditions after administration of a HFD [ 25 ].…”
Section: Discussionmentioning
confidence: 99%